Christianity and Social and Cultural Changes in Li and Miao Settlements in Hainan in Modern Times - TAN, Hui (Journal of Research for Christianity in China (JRCC), 2025)
After the Second Opium War, Qiongzhou was opened as a trading port. Since then, the number of foreigners in Qiong has increased, which has become an important factor affecting the social changes in modern Hainan. In 1881, the first Protestant missionary, Carl C. Jeremiassen, came to Hainan, and the Protestant missionary career in Qiong began. In the early days, missionaries carried out missionary activities based on the densely populated areas of Han nationality, and at the same time carried out investigations on the inland areas of Li and Miao nationality in Hainan. With the increasing influence, the missionaries then adopted a series of missionary activities to introduce Christianity into the settlements of the Li and Miao nationalities in Hainan. Affected by this, the Hainan Li and Miao nationalities have undergone varying degrees of changes in religious beliefs, cultural education, and medical concepts. This change shows the modernization trend of the social and cultural changes of the Li and Miao ethnic groups under the influence of heterogeneous culture.